Antropofagia e o seu sabor sagrado: ressignificações e contribuições no processo de construção de uma identidade brasileira - Lima, Tatiane Ribeiro de (2015)
In this present study, we will try to show the ways the anthropophagy went through in Brazil since the colonizers arrival until the way we treat the subject nowadays throughout our society. For that, we will use the ethnographic reports and the explorers’ history chronicles from the centuries XIV and XV as the stydy parameter, where they detail the anthropophagy rituals seen in the new world. However, we will comply with the narratives which specifically observed the Tupinambá behaviour. The reports analysis will show us how the anthropophagy was seen and treated by the Europeans at the first moment. Then, we will try to show how the anthropophagy was lived by the Brazilian people and where this extinct religious tradition found space to survive into the brazilian culure and imagination. Since the period of colonization until today the anthropophagy handled a long and hard way, seen as an absurd animality as well as a cultural taboo, or something to be ignored, usually not well seen or misunderstood. We still have, into our collective unconscious, the same ideas the explorers had about cannibalism at the discovery period. In this study, we intend to bring up a new vision, show the other side, the indian version of anthropophagy, not as an act of animality but as an integral part of their religious life as well as a crucial part for the national identity formation. For that, we will use, as a method of analysis and support, the symbolic eliadian hermeneutics and the General Theory of the Imaginary, by Gilbert Durand. With those, we show where the sacred is, considering the indian anthropophagy rituals and also where the sacrad anthropophagy is in our society, demonstrating that the sentence “ We are all cannibals” by the French anthropologist Lévi-Straus perfectly fits the Brazilian profile, specially because the anthropophagy is still present whithin the Brazilians.